Takeovers Improve Firm Performance: Evidence from the Banking Industry - Schranz, Mary S. (Journal of Political Economy, 1993)
The hypothesis that takeovers provide managers with the incentive to maximize firm value is tested by examining the relationship between profitability and state statutes governing takeover activity among banks. The evidence indicates that firms in states with an active takeover market are more profitable. When takeover activity is restricted, increased use of other mechanisms that provide an incentive to maximize firm value, such as concentration of equity ownership and management ownership of stock, is observed. However, these alternative methods have a smaller effect on profitability and do not completely compensate for the absence of an active takeover market.